Photoexcitation Dynamics of Cyanate-ligated Ferric Heme Proteins Probed by Femtosecond Vibrational Spectroscopy - Park, Seongchul; Park, Jaeheung; Jang, Joonkyung; Lim, Manho (Bulletin of the Korean Chemical Society, 2015)
The photoexcitation dynamics of cyanate‐ligated ferric myoglobin (MbNCO) and hemoglobin (HbNCO) in D2O at 293 K after excitation with a visible pulse was investigated by probing the anti‐symmetric stretching (ν1) mode of the NCO − ion bound to Mb or Hb using femtosecond vibrational spectroscopy. The ν1 mode of NCO in MbNCO or HbNCO in D2O shows one absorption feature near 2158 cm−1, which is similar to that of the free anion in D2O (2160 cm−1). The absorption feature of MbNCO was described by two absorption bands, i.e., one major band (90%) peaked at 2157 cm−1 with a full width at half maximum (FWHM) of 11 cm−1 and a minor band (10%) at 2143 cm−1 with an FWHM of 12 cm−1. In HbNCO, the major (82%) and minor (18%) bands are at 2159 (FWHM of 14 cm−1) and 2145 cm−1 (FWHM of 14 cm−1), respectively. The major and minor bands were attributed to the high‐ and low‐spin heme complexes, respectively. The photoexcited MbNCO and HbNCO undergo a rapid electronic relaxation with a time constant smaller than 0.4 ps, followed by thermal relaxation with a time constant of 8 ± 1 ps. No measurable absorption band for the photodeligated NCO − was detected, indicating that the photodeligation quantum yield of NCO −‐bound ferric heme proteins is negligible. The characteristics of the thermal and electronic relaxations are independent of both the excitation wavelengths used (575 and 400 nm) and heme proteins probed (Mb and Hb). Although the interaction between the cyanate and Fe3+ of the heme in Mb and Hb may be weak as suggested by the negligible shift in the band position of the cyanate upon ligand binding, the photodissociation of NCO − by a visible pulse is not significant. This finding is consistent with the negligible photodeligation observed for most of the other anion‐ligated ferric heme proteins.